Pengembangan Keterampilan Menulis Teks Eksposisi dengan Metode Problem Based Learning pada Siswa di Sekolah Dasar - Adela Khalisa Fitri; Daranda Dwifarzah; Nurul Fathia; Raisa Hanifa (Politeknik Kampar, 2024)
Development of Expository Writing Skills in Elementary School Students Can Be Achieved Through Problem-Based Learning (PBL). PBL Enables Students to Think Critically, Communicate Effectively, and Develop Problem-Solving Skills. Research Findings Show That PBL Is Effective in Enhancing Expository Writing Skills, Both in Structure, Style, and Content. PBL Also Boosts Students' Motivation in Writing Expository Texts. Therefore, Using PBL as a Strategy for Developing Expository Writing Skills in Elementary School Students Can Help Improve Learning Outcomes and Enhance Writing Quality